Initial teacher training: Validation of a competence reference framework for the training of mentor teachers/cooperating teachers - Baco, Christophe; Derobertmasure, Antoine; Bocquillon, Marie; Demeuse, Marc (Frontiers in Education, 2023)
Throughout the world, cooperating teachers are crucial for initial teacher training. This article proposes a double validation of a competence reference framework for the training of cooperating teachers. This validation is based, on the one hand, on international literature and, on the other hand, on the analysis of the answers of 854 French-speaking Belgian cooperating teachers to a questionnaire on the ideal level of proficiency in the tasks inherent to their function. The results indicate a strong convergence between the proposed competence reference framework, the literature review and the opinion of the 854 cooperating teachers.